2022
DOI: 10.1002/adma.202205154
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profiling and Multiplexed Label‐Free Detection of 2D MXenes by Mass Cytometry and High‐Dimensional Imaging

Abstract: There is a critical unmet need to detect and image 2D materials within single cells and tissues while surveying a high degree of information from single cells. Here, a versatile multiplexed label‐free single‐cell detection strategy is proposed based on single‐cell mass cytometry by time‐of‐flight (CyTOF) and ion‐beam imaging by time‐of‐flight (MIBI‐TOF). This strategy, “Label‐free sINgle‐cell tracKing of 2D matErials by mass cytometry and MIBI‐TOF Design” (LINKED), enables nanomaterial detection and simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In particular, DCs showed the most prominent binding to these MXenes. 264 To sum up the literature to date, it remains challenging to conclusively determine the specific immune impact of 2D materials even within their individual subclasses due to minute differences in their manufacturing process, structure, functionalization or dispersibility profile, which could lead to various possibilities of cell interaction and downstream response. Macrophages remain the most popular immune cell of investigation due to their role as a key phagocytic cell of the innate immune system, as well as ease of culture.…”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, DCs showed the most prominent binding to these MXenes. 264 To sum up the literature to date, it remains challenging to conclusively determine the specific immune impact of 2D materials even within their individual subclasses due to minute differences in their manufacturing process, structure, functionalization or dispersibility profile, which could lead to various possibilities of cell interaction and downstream response. Macrophages remain the most popular immune cell of investigation due to their role as a key phagocytic cell of the innate immune system, as well as ease of culture.…”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
“…Among the tested materials, Nb 4 C 3 displayed the strongest signal and extensive cellular interaction could be detected. In particular, DCs showed the most prominent binding to these MXenes …”
Section: D Materials and Adaptive Immunitymentioning
confidence: 99%
“… 21 , 48 Recently, high-dimensional immune and functional profiling of Nb 4 C 3 , Mo 2 Ti 2 C 3 , and Ta 4 C 3 T x has revealed that these forms of MXenes do not affect immune cell functionality and have excellent biocompatibility. 65 Furthermore, these MXenes possess intrinsic immunomodulatory properties that facilitate engineering the immune and inflammatory response of different cells and tissues (Figure 3 e). 60 , 61 For example, treating activated cocultures of human umbilical vein endothelial cells (HUVECs) and interferon-gamma (IFN-γ) expressing T-lymphocytes with Ta 4 C 3 T x QDs significantly reduced the percentage of IFN-γ + T-lymphocytes, indicating successful immunomodulation.…”
Section: Tissue Engineering and Immunomodulation With Mxenesmentioning
confidence: 99%
“…9 Other forms of MXenes, such as Nb 4 C 3 , Mo 2 Ti 2 C 3 , and Ta 4 C 3 T x are gaining traction for immunomodulation due to their excellent biocompatibility and intrinsic immunomodulatory properties. 65 …”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation